Analysis of Green Investment Awareness, Climate Risk Perception, and Profitability Expectations on Millennials' Sustainable Investment Decisions in Indonesia - Shella Kriekoff (Westscience Press, 2026)
This study investigates the influence of green investment awareness, climate risk perception, and profit expectations on sustainable investment decisions among millennials in Indonesia. As sustainable finance continues to expand, understanding the behavioral factors that drive individual investors—particularly younger generations—has become increasingly important. This research adopts a quantitative approach using primary data collected from 185 millennial respondents through a structured questionnaire measured on a Likert scale. The data were analyzed using SPSS version 25, employing descriptive statistics and multiple linear regression analysis. The results reveal that green investment awareness has a positive and significant effect on sustainable investment decisions, indicating that greater knowledge and understanding of environmentally friendly investment instruments encourage millennials to invest sustainably. Climate risk perception is also found to have a significant positive influence, suggesting that heightened awareness of climate-related risks motivates millennials to consider sustainability aspects in their investment choices. Additionally, profit expectations show the strongest positive effect, confirming that financial return considerations remain a crucial determinant of sustainable investment behavior. Overall, the findings demonstrate that a combination of environmental awareness, risk perception, and economic rationality shapes millennials’ sustainable investment decisions in Indonesia. This study contributes to the literature on sustainable finance and provides practical insights for policymakers and financial institutions in promoting sustainable investment among younger generations.